LENGTH OF VEGETATION PERIOD AND FRUIT SET IN PEPPER GROWN ON DIFFERENT TYPES OF MULCH - Zvezda Bogevska; Gordana Popsimonova; Rukie Agic; Margarita Davitkovska; Daniela Trajkoska; Maja Sudimac (Ss Cyril and Methodius University in Skopje, Faculty of Agricultural Sciences and Food - Skopje, 2022)
Mulching is a common practice of covering the soil to make favorable conditions for plant growth, development, and efficient crop production. The study aimed to determine the influence of different mulching materials on some parameters of pepper Kapija type grown in an open field. The experiment was set in the village of Kutretino near Demir Hisar, during the season of 2018. The treatments were as follows: no mulch (bare soil) - as a control treatment, straw mulch, black film mulch, white on black (double face) film mulch, and red film mulch. A single experimental plot was 15 m2 with a density of 100 plants per plot organized in a complete randomized block design in four replications. During the vegetation, there was monitoring of some phenological stages. In addition, on ten plants per replication, the number of flowers and the number of fertilized flowers were recorded. The earlier botanical maturity was in straw mulch and black foil mulch or 153 days after germination. The latest was in red foil mulch or 161 days after germination. The largest number of flowers had the plants from the black foil mulch an average of 11.83 flowers, out of which 10.95 were fertilized, which means that 92.56% of the flowers set fruit. Plants on red mulch had the least number of flowers, 7.33 on average, of which 5.73 were fertilized, leading to 78.17% of fruit set. White on black mulch had the highest percentage of fruit set (93.7%) because of favoring condition.
Keywords: foils, straw, earliness, number of flowers, number of fertilized flowers